Classification Methods for Inland Excess Water Modeling - van Leeuwen, Boudewijn; Henits, László; Mészáros, Minucsér; Tobak, Zalán; Szatmári, József; Pavić, Dragoslav; Savić, Stevan; Dolinaj, Dragan (Journal of Environmental Geography, 2013)
Inland excess water floodings are a common problem in the Carpathian Basin. Nearly every year large areas are covered by water due to lack of natural runoff of superfluous water. To study the development of this phenomenon it is necessary to determine where these inundations are occurring. This research evaluates different methods to classify inland excess water occurrences on a study area covering south-east Hungary and northern Serbia. The region is susceptible to this type of flooding due to its geographical circumstances. Three separate methods are used to determine their applicability to the problem. The methods use the same input data set but differ in approach and complexity. The input data set consists of a mosaic of RapidEye medium resolution satellite images. The results of the classifications show that all three methods can be applied to the problem and provide high quality satellite based inland excess water maps over a large area.